Performance Baseline and Recommendations for the Development of Islamic Education at MTsN 3 Surabaya - Putri, Natasya Risma; Aisyah, Nasya'a Nadyah; Mardiyah, Mardiyah (Indonesian Journal of Education and Mathematical Science, 2025)
This study aims to analyze the baseline of performance achievements, the implementation of Madrasah Self-Evaluation (EDM), and formulate recommendations for the development of Islamic education in MTsN 3 Surabaya. This study uses a qualitative approach through field and analytical descriptive methods. Data were collected through observation, interviews, documentation, and literature review. The results of the study show that MTsN 3 Surabaya has a structured and good performance baseline, and has the trust of the community. The implementation of EDM routinely has a significant impact on improving the quality of madrasas. Recommendations for educational development formulated after EDM have proven to be relevant and support the growth of madrasas. However, there are still challenges in terms of funding and infrastructure optimization. Madrasah recommends several developments, including improving teacher competence, building and renovating facilities such as libraries, laboratories, and health facilities. In addition, religious programs are also offered to strengthen the identity of Islamic education. With structured management and the right strategy, MTsN 3 Surabaya is expected to continue to develop as a superior Islamic educational institution, adaptive to the changing times, and able to produce a balanced generation between science and Islamic values.